Infliximab Therapy Could Decrease the Risk of the Development of Thyroid Disorders in Pediatric Patients With Crohn's Disease - Furtak, Aleksandra; Wedrychowicz, Anna Maria; Sladek, Malgorzata; Wedrychowicz, Andrzej; Fyderek, Krzysztof; Starzyk, Jerzy (Frontiers in Endocrinology, 2020)
Autoimmune diseases, including autoimmune thyroid diseases (AITD), may be associated with Crohn's disease (CD). Taking to consideration the role of tumor necrosis factor alfa (TNF-alfa) in the immune mediated inflammation, that underlies both diseases, we evaluated an ultrasound of thyroid gland in paediatric CD patients, naïve and treated with infliximab, an anti-TNF-alfa antibody, to assess the risk for AITD and evaluate usefulness of ultrasonography to diagnose AITD in patients with CD. Sixty-one patients with CD were enrolled in the study, including 36 patients (mean age 14.5±3.5 years) treated with infliximab (IFX group) for mean 13.9±16.6 months, and 25 patients (mean age 14.7±2.3 years) never received anti-TNF-alpha therapy (control group). An ultrasound examination of the thyroid gland were performed, thyroid function tests and thyroid antibodies were assessed. We found 10-times higher prevalence of decreased thyroid echogenicity in CD and IFX naïve patients compare to IFX treated group (a significant reduction in thyroid echogenicity in 1/36 (2.8%) patients receiving infliximab compare to 7/25 (28%) patients naïve to biologic therapy). The latter, showed significantly lower TSH levels (p=0.034) and higher levels of thyroid antibodies (p = 0.042) in comparison to control. Our data suggest the protective role of infliximab therapy in the development of thyroid disorders and indicate usefulness of thyroid ultrasound to identify the risk of probable AITD in pediatric patients with CD.